Primary hyperparathyroidism presenting as acute hypercalcemic crisis: a case report - Gia Gill; Veena Agrawal; Paul Kerr (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Hyperparathyroid crisis, or “parathyroid storm” is a rare manifestation of primary hyperparathyroidism, characterized by sudden onset of symptomatic, severe hypercalcemia (> 3.5 mmol/L). Hemorrhage into a parathyroid adenoma has rarely been reported as an inciting or associated event. We present a case of hemorrhage into a longstanding adenoma presenting with acute onset of profound hypercalcemia and associated complications. Case presentation A 60-year-old male presented to hospital with sudden onset of confusion, muscle weakness, and ataxia. Initial labs showed serum calcium 4.79 mmol/L, parathyroid hormone 2043 ng/L; creatinine 364 μmol/L. Review of the patient’s medical history indicated a 4-year history of recurrent nephrolithiasis, but no prior documented calcium levels. The hypercalcemia did not respond to 5 days of aggressive medical management with fluid resuscitation, denosumab and calcitonin, and later pamidronate and cinacalcet. He continued to deteriorate, requiring intubation and continuous renal replacement therapy. Imaging demonstrated 4.8 cm cystic right paratracheal mass; Technetium (Tc99m) Sestamibi scintigraphy was non-localizing. Urgent parathyroidectomy was completed, revealing a 5 × 3.3 × 1.8 cm hemorrhagic, atypical hypercellular parathyroid. Unfortunately, the patient died from complications from anticoagulation therapy for treatment of deep vein thrombosis 4 weeks after admission. His renal function had not recovered at the time of his death. Conclusion This case gives potential insight into the etiology of hyperparathyroid crisis, and the difficulty in achieving control of hypercalcemia with medical means. Surgical intervention is the definitive management in these cases and should be considered urgently. Graphical Abstract